The Implementation Gap in the Legal Validity of Marriage in Indonesia: A Socio-Legal Study of Baduy Customary Marriage - RD I Mulyana Jaya Sumpena; Wahyuni Retnowulandari; Endang Pandamdari (Penerbit Mandalika Indonesia, 2026)
Legal pluralism in Indonesia has not yet been fully integrated into the implementation of national marriage law, particularly in relation to indigenous communities. This study examines the implementation gap between state legality and customary legitimacy within the Baduy indigenous community. Employing a qualitative socio-legal approach through literature review, normative analysis, and empirical understanding of customary practices, the study finds that the validity of marriage under national law is determined by compliance with religious requirements and administrative registration. In contrast, the Baduy community regards a marriage as valid through customary ceremonies and communal legitimacy as part of the living law. This divergence creates legal uncertainty and administrative exclusion, affecting civil registration, identity documentation, and access to public services. A comparative analysis involving the Ammatoa Kajang, Marapu, and Māori communities demonstrates that adaptive recognition mechanisms can facilitate the integration of customary law and state law. The study concludes that the Indonesian legal system remains predominantly legal-formalist and has not yet fully accommodated the realities of legal pluralism. Therefore, a more inclusive and responsive legal approach is required to integrate living law into the national legal system while ensuring equal legal protection for indigenous peoples.